Anxiolytic and Potential Neurotoxic Effects of Salvia hypoleuca in Mice - Talebi, Marjan; Alinejad, Reyhaneh; Naderi, Nima; Mojab, Faraz (Iranian Journal of Pharmaceutical Sciences, 2025)
Anxiety disorders are prevalent worldwide, significantly impacting various aspects of patients’ lives. The use of Salvia species in ethnobotanical medicine has been well documented, with applications as diuretics, analgesics, anti-hyperhidrosis agents, laxatives, antipyretics, and antitussives. Among these, Salvia hypoleuca, an endemic plant in Iran, is recognized for its tonic, carminative, digestive, antispasmodic, anti-inflammatory, antioxidant, antimicrobial, and anti-nociceptive properties. The objectives of this study were to assess the anxiolytic effects of S. hypoleuca ethanolic extract and its potential neurotoxicity using established pharmacological models in mice. Animals were randomly allocated into five groups: one control group, three groups underwent treatment that received oral doses of S. hypoleuca at 30, 100, and 300 mg/kg, and a positive control group given diazepam at 10 mg/kg. Behavioral evaluations were performed using the light/dark test (LDT) and the elevated plus maze (EPM) tests. To evaluate potential neurotoxic effects, open-field and rotarod tests were also performed. The results specified that S. hypoleuca extract at doses of 30 and 100 mg/kg significantly enhanced entries and time spent in the open arms of the EPM, suggesting anxiolytic effects. In the LDT, the 30 mg/kg dose notably increased the time spent in the light box. However, the rotarod test showed a slight decrease in latency to fall at both 30 and 300 mg/kg doses, indicating possible motor impairment at higher concentrations. Open-field analysis revealed significant reductions in total distance moved and velocity at 30 and 300 mg/kg doses, suggesting potential locomotor suppression. Additionally, the total phenolic and total flavonoid contents of S. hypoleuca ethanolic extract were measured as 47.26 ± 2.87mg GAE/g DW and 31.73 ± 5.38 mgRE/g DW, respectively. In conclusion, our efforts suggest that oral administration of S. hypoleuca extract exhibits anxiolytic effects in mice, as demonstrated by improved performance in the EPM and LDT. However, the observed locomotor impairment at higher doses warrants further investigation to determine the optimal therapeutic dose and potential safety concerns.